Research on the application of chess teaching in the intellectual development of young children: analysis of educational models and strategies - Ye, Yuhan (Frontiers in Psychology, 2025)
This study investigates the application of chess teaching in the intellectual development of young children, focusing on its impact on cognitive abilities, emotional resilience, and academic performance. Through a quasi-experimental design, two kindergartens (Kindergarten A and Kindergarten B) were selected to explore the effectiveness of different chess teaching models: Kindergarten A adopted a classroom integration model, while Kindergarten B implemented an extracurricular interest class model. Pre-tests and post-tests were conducted to assess changes in children’s abilities across both groups. Results from independent samples t-tests revealed significant improvements in attention, memory, logical thinking, patience, self-discipline, mathematics scores, and reading scores among children in the experimental groups compared to the control groups (p< 0.001). These findings highlight the positive effects of chess teaching on the comprehensive development of young children, demonstrating its potential as an educational tool. The study provides valuable recommendations for integrating chess into early childhood education, advocating for teacher training, parental involvement, and tailored instructional programs to maximize benefits for children’s intellectual development. In conclusion, chess teaching emerges as a powerful tool for enhancing the cognitive, emotional, and academic growth of young children. Its integration into educational practices is recommended to support holistic development.